First insights into micromorphology of needle epicuticular waxes of south-eastern european Pinus nigra J. F. Arnold populations - Mitić, Zorica S.; Zlatković, Bojan K.; Miljković, Miroslav S.; Jovanović, Snežana Č.; Marin, Petar D.; Stojanović, Gordana S. (Iheringia, Série Botânica., 2018)
This is the fi rst insight into the fi ne structure of the epicuticular wax crystalloids found on the adaxial surfaces of needles from three Pinus nigra subspecies (ssp. nigra, ssp. banatica (Borbás) Novák, and ssp. pallasiana (Lamb.) Holmboe) growing wild in the south-eastern Europe. In general, the main wax crystalloids in P. nigra taxa were tubules, fairly dense, with reticular aspect and restricted to suprastomatal chambers. The P. nigra needles have amorphous wax - smooth layers, granules, alone tubes lying on the surface, tubes slightly fused to each other, tubes fused together, and longitudinally aggregated rodlets. The only diff erence between the studied P. nigra samples was related to the presence of longitudinally aggregated rodlets in the medial part of adaxial needle surfaces. The micromorphological characters found using SEM are compared and discussed from fundamental and applicative aspects.